An investigation of the malaysian palm oil industry's environmental strategies, stakeholders' pressure, environmental effectiveness and competitive advantage. - Mohd Rafi Yaacob (Universiti Malaya, 2011)
Malaysia palm oil is the most important agricultural commodity in the country, and contributes substantially to the economy. Unfortunately, its activities are not without environmental cost.